Prevalence Study of Patients with Upper Extremity Masses (Annals of Medical Research, 2021)
Aim: The soft tissue and bone tumors which are located in the upper extremity usually have a benign character.  These lesions which require careful diagnosis and treatment are mostly studied retrospectively and in small series. In this study, we aimed to evaluate the relations of the tumors located in the upper extremity by age, gender, mass location, clinical and pathological diagnosis and their compliance with these diagnoses.
Keywords: Benign; Extremity; Malign; Biopsy; Tumor.